2015
DOI: 10.1007/s00464-015-4508-z
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota and anastomotic leakage of stapled colorectal anastomoses: a pilot study

Abstract: Background Anastomotic leakage (AL) after colorectal surgery is a severe complication, resulting in morbidity, reinterventions, prolonged hospital stay and, in some cases, death. Some technical and patient-related aetiological factors of AL are well established. In many cases, however, none of these factors seem to explain the occurrence of AL. Recent studies suggest that the intestinal microbiome plays a role in wound healing, diabetes and Crohn’s disease. The aim of this study was to compare the intestinal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 32 publications
2
46
1
Order By: Relevance
“…The extracted DNA was amplified and processed as previously described (27). Briefly, primers covering the V3 and V4 hyper V region of the bacterial 16S rRNA genes were used.…”
Section: Microbiota Analysis Of Fecal Samplesmentioning
confidence: 99%
“…The extracted DNA was amplified and processed as previously described (27). Briefly, primers covering the V3 and V4 hyper V region of the bacterial 16S rRNA genes were used.…”
Section: Microbiota Analysis Of Fecal Samplesmentioning
confidence: 99%
“…The microbiome of eight patients who experienced colorectal anastomotic rupture and of another eight matched for age, gender and adjuvant therapy, was investigated by studying the rings of colon and rectum tissues cut by the circular stapler to make the anastomosis [62]. The investigators surprisingly reported a significantly higher proportion of the Lachnospiraceae family versus controls-although these bacteria tend to be rather friendly to the bowel, as most of them belong to butyrate producing genera.…”
Section: Intestinal Microbiota: Symbiosis and Dysbiosismentioning
confidence: 99%
“…The C-seal is a biodegradable sheath that protects the stapled colorectal anastomosis from leakage 101. The researchers compared the mucosa-associated microbiota collected at the anastomosis level during the surgical intervention from eight patients who developed AL requiring reintervention with that of matched individuals from the same trial who had a favourable evolution 102. They found a correlation between the bacterial family Lachnospiraceae , low microbial diversity and AL, possibly in association with the body mass index.…”
Section: Influence On and Changes In The Gut Microbiota After Intestimentioning
confidence: 99%